2010
DOI: 10.2166/hydro.2010.142
|View full text |Cite
|
Sign up to set email alerts
|

A new wavelet–bootstrap–ANN hybrid model for daily discharge forecasting

Abstract: A new hybrid model, the wavelet-bootstrap-ANN (WBANN), for daily discharge forecasting is proposed in this study. The study explores the potential of wavelet and bootstrapping techniques to develop an accurate and reliable ANN model. The performance of the WBANN model is also compared with three more models: traditional ANN, wavelet-based ANN (WANN) and bootstrapbased ANN (BANN). Input vectors are decomposed into discrete wavelet components (DWCs) using discrete wavelet transformation (DWT) and then appropriat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(37 citation statements)
references
References 81 publications
1
35
0
1
Order By: Relevance
“…The bootstrap method is a simple algorithm which can be used to account for uncertainty. The combination of WA‐bootstrap‐ANN has been successfully used in other areas of hydrological forecasting [ Tiwari and Chatterjee , 2010a, 2010b], and the possible use of this method in water demand forecasting appears promising and will be studied further by the authors. In addition, there is little research available on the MNLR method in water demand forecasting.…”
Section: Resultsmentioning
confidence: 99%
“…The bootstrap method is a simple algorithm which can be used to account for uncertainty. The combination of WA‐bootstrap‐ANN has been successfully used in other areas of hydrological forecasting [ Tiwari and Chatterjee , 2010a, 2010b], and the possible use of this method in water demand forecasting appears promising and will be studied further by the authors. In addition, there is little research available on the MNLR method in water demand forecasting.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the bagged SVM model outperforms the prediction ability of bagged multiple linear regressions (MLRs), simple SVM, and simple MLR models in all of the adopted evaluation scores. Tiwari and Chatterjee (2011) investigated hybrid wavelet bootstrapped artificial neural networks models in daily discharge forecasting. The results revealed that the model which uses the capabilities of both bootstrap and wavelet methods was the best model.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the simplicity of W 1 (t), W 2 (t) …, W l (t), the relevant characteristics in the hydrologic dataset (e.g. periods, hidden periods, dependence and jumps) can be diagnosed through these discrete wavelet components [TIWARI, CHATTERJEE 2011]. Consequently, the prediction accuracy of drought models are improved.…”
Section: Discrete Wavelet Transformationmentioning
confidence: 99%